The GenARDIS Fund - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A Small Grants Fund in the field of gender and information and communication technologies (ICTs) has been launched by CTA, the International Development Research Centre (IDRC) and the International Institute for Communication and Development (IICD)....